2019
DOI: 10.7717/peerj.6665
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic comparison of quercetin, isoquercitrin, and quercetin-3-O-β-D-glucuronide in rats by HPLC-MS

Abstract: Background Quercetin (Qr), isoquercitrin (IQ), and quercetin-3-O-β-D-glucuronide (QG) are powerful phytochemicals that have been shown to exhibit disease prevention and health promotion properties. However, there may exist transformations between Qr, IQ, and QG in vivo. And the pharmacokinetic profiles of Qr, IQ, and QG have not been systematically compared. The pharmacokinetics study would be helpful to better understand the pharmacological actions of them. Methods Herein, we developed a reliable HPLC-MS me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Quercetin in foods is bound to sugars, mainly as β-glycosides, whose bioavailability is affected by their sugar moiety. Isoquercitrin’s bioavailability is only 5% of that observed with QUE, and in the gut, it is rapidly metabolized to QUE by β-glucosidases [102]. This suggests that the systemic and local (in the gut) effects of QUE (glucoside)-rich food are predominantly anti-carcinogenic by targeting glycolysis.…”
Section: Anti-cancer Effect Of Quercetin By Targeting Key Moleculamentioning
confidence: 99%
“…Quercetin in foods is bound to sugars, mainly as β-glycosides, whose bioavailability is affected by their sugar moiety. Isoquercitrin’s bioavailability is only 5% of that observed with QUE, and in the gut, it is rapidly metabolized to QUE by β-glucosidases [102]. This suggests that the systemic and local (in the gut) effects of QUE (glucoside)-rich food are predominantly anti-carcinogenic by targeting glycolysis.…”
Section: Anti-cancer Effect Of Quercetin By Targeting Key Moleculamentioning
confidence: 99%
“…Quercetin is a natural avonoid, quercetin (Qr), isoquercitrin (IQ), and quercetin-3-O-β-D-glucuronide (QG) were also mutual transform in vivo. The t1/2 of quercetin is about 437min [65]. And studies have shown that QG is a major active component in plasma and tissue for oral administration of Qr or QG [66].…”
Section: Experiments Resultsmentioning
confidence: 99%
“…Quercetin is a natural flavonoid, quercetin (Qr), isoquercitrin (IQ), and quercetin-3-O-β- d -glucuronide (QG) were also mutual transform in vivo. The t1/2 of quercetin is about 437 min [ 65 ]. And studies have shown that QG is a major active component in plasma and tissue for oral administration of Qr or QG [ 66 ].…”
Section: Discussionmentioning
confidence: 99%